Bananas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
'Bunchy Top' and 'Black Stripe' disease are two of the main enemies of banana production. Resistant varieties exist but the problem is how to make them available in sufficient quantities. A propagation method based on tissue cultures has just been...